EFFORTS TO INCREASE STUDENTS' INTEREST IN TRADITIONAL SPORTS THROUGH SCOUT TRAINING METHODS FOR SMP NEGERI 2 MOJOGEDANG SCHOOL YEAR 2019/2020 - Teguh Santosa; Joko Sulistiyono; Razali, (Journal Of Indonesia Sport Education and Adapted Physical Education (JISEAPE), 2022)
The purpose of this research : to determine student”s interest in traditional sports through the souts training method and effort to preserve traditional method by playing it back while introducing traditional sports in students SMP Negeri 2 Mojogedang school year 2019/2020.The research method used is qualitative methods by the type of survery research. population in this research is a class students VII SMP Negeri 2 Mojogedang which amount to 220 students. Sampling technique by using purposive sampling technique. So the sample in this research as much 30 students from the class VII SMP Negeri 2 Mojogedang. data collectiom technique a questionnaire. Research analysis technique using descriptive analysis with a percentage.The research result show that through the scout training method can increase student’s interest in traditional sports amounting to 6,93% where before using scouts method student’s interest in traditional sports amounting to 68,70%, then after using scout method student’s interest in traditional sports increase to be 75,63%. The conclusion of this research is to use scout training method student can increase interest in traditional sports at SMP Negeri 2 Mojogedang year 2020